Formation Mechanism of a Coastal Zone Environment Collaborative Governance Relationship: A Qualitative Comparative Analysis Based on fsQCA - Wang, Wanjuan; Gong, Hongbo (International journal of environmental research and public health, 2022)
The coastal zone is an area where terrestrial and marine ecosystems intersect. This region may be subject to outstanding environmental issues, as influenced by many stakeholders. Based on the framework of collaborative governance, the starting conditions for forming a coastal zone environment collaborative governance relationship are proposed as follows: coastal zone environment, balanced level of power and resources, superior-level government participation, and previous cooperation experience. The coastal environmental governance practices of 14 cities along the continental coastal zone of the East China Sea are selected as cases, in order to test the interactions between and influence mechanisms of the starting conditions. As qualitative comparative analysis (QCA), based on set theory and Boolean algebra, is a popular tool to explain complex collaboration situations in small-N cases; and as fuzzy-set qualitative comparative analysis (fsQCA) allows for fine classification of the membership degree (where the condition can be allocated any number between 0 and 1), we use fsQCA to analyze the collaborative governance relationships. The results of the analysis demonstrate that three combination configurations promote the formation of medium–high intensity collaborative governance relationships: high balance level of power and resources × high previous cooperation experience, high pollution of coastal zone environment × high balance level of power and resources × low superior-level government participation, and high pollution of coastal zone environment × high superior-level government participation × high previous cooperation experience. Based on this conclusion, we determine three types of relationship formation modes: wheel-, echo state network-, and umbrella-shaped modes. Notably, under certain conditions, superior-level government participation is not necessary for the formation of a medium–high intensity collaborative governance relationship.